2014
DOI: 10.4269/ajtmh.13-0398
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences of Visceral Leishmaniasis Caused by Leishmania siamensis after Treatment with Amphotericin B in a Seronegative Child

Abstract: Abstract. We report the first case of visceral leishmaniasis caused by Leishmania siamensis in a seronegative child. She was treated with amphotericin B at 1 mg/kg/day for 3 weeks; however, recurrences occurred twice. The patient was cured after the administration of amphotericin B for 5 weeks and monthly prophylaxis for 6 months. CASE REPORTIn 2008, a 5-year-old girl living in a rural area of Satun Province, southern Thailand came to a provincial hospital because of abdominal enlargement for 2 months. Her con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Leishmania sp. 'siamensis', as a cause of human VL, predominantly in immunosuppressed patients [6770]. As discussed by other investigators [46], Leishmania 'siamensis' represents a nomen nudum , and is shown inverted commas here as a consequence.…”
Section: Discussionmentioning
confidence: 81%
“…Leishmania sp. 'siamensis', as a cause of human VL, predominantly in immunosuppressed patients [6770]. As discussed by other investigators [46], Leishmania 'siamensis' represents a nomen nudum , and is shown inverted commas here as a consequence.…”
Section: Discussionmentioning
confidence: 81%
“…Leishmania siamensis, a species recently reported in Thailand, causes both cutaneous and visceral leishmaniasis especially in patients with immunocompromised conditions such as HIV/AIDS [2][3][4][5][6]. In addition, leishmaniasis caused by L. siamensis was also reported in animals [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…siamensis have been identified and genetically characterized using several target genes [2][3][4][5][6]. However, diagnosis of L. siamensis infection using PCR methods based on different genetic markers has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the reported cases have come from southern Thailand, and the first confirmed autochthonous case was reported from this region in 1999, presenting as visceral leishmaniasis in a 3‐year‐old girl native to Surat Thani Province and who had never been abroad . Since then, several further cases have been reported from southern Thailand, including some with HIV co‐infection, and some of these with mixed symptomology of visceral and cutaneous leishmaniasis . The first case in northern Thailand, a 40‐year‐old man from Nan Province, was reported in 2005, and the second, a 52‐year‐old man from Lamphun Province, in 2012 .…”
mentioning
confidence: 99%